Isotomidae (Collembola) of Buryat Republic. III. The genera Vertagopus and Agrenia, with a note on 'Claw index' - Potapov, Mikhail; Gulgenova, Ayuna; Babykina, Marina (Zootaxa, 2016)
Two genera are revised based on material from Buryatia (Russia, East Siberia). Vertagopus ceratus sp. nov. and V. asiaticus sp. nov. are described of which the former species is strictly alpine and is defined by pale colouration, the presence of chaetae on the anterior side of the ventral tube, and abundant sensillar chaetotaxy. V. asiaticus sp. nov. is widely distributed in Asia and is unusual due to only 9 chaetae in apical whorl on tibiotarsi. A key to species of Vertagopus Börner, recorded in the republic is given, and notes on morphology, distribution, and ecology are provided. In the genus Agrenia Börner, a form similar with A. bidenticulata was recorded in mountainous areas. Buryatian populations considerably differ from the diagnosis of the typical arctic A.bidenticulata (Tullberg) by a much longer claw. A conception of A. bidenticulata sensu lato complex is temporarily proposed basing on available materials from Palearctic, including High Arctic, sub-Arctic and South Siberian mountains. The complex consists of several local forms which are different in Claw index and associated Tibiotarsus/Claw ratio, while the dependence of the two indexes on the latitude is shown.